Manifestations of Media Incitement to Violence in Iraqi Satellite Channels- Out of the Iraqi Media's View. - Jassim, Abdel Nabi Khazal; Hameed, Shareef Saeed (ALBAHITH ALALAMI, 2015)
representing the media and communication problems and phenomena fertile material and of great importance in the media research, especially as they relate to various aspects of life and its impact on the culture of the community and on individuals and public opinion about the behavior of the various issues. The media incitement to violence and hatred of the most prominent media phenomena that increased the danger and expanded not at the local level, but also in the world. So we found it is important to study this problem from the standpoint of academic and professional. And according to the progress of this research is trying to answer a number of questions including: A. What are the Iraqi Satellite TV channels most watched and follow-up by the ethnic media as sources of information on Iraqi affairs? What are the most incitement to violence and the degree of incitement practiced channels? B. What are the most prominent manifestations and methods of incitement to violence and the degree of incitement and most types of programs addressed in this incitement topics? C. What are the points of incitement to violence and what are the sources of guidance D. What are the main trends that tend her satellite programs when covered daily events? This is the search of a descriptive research survey method has been used in the context of what is associated scans the audience and the media. And took the search several areas, representing the spatial field in Iraqi Satellite TV channels specifically, while representing the temporal sphere duration from the beginning of March to the end of the month of April of 2014, and represents the human field to search workers in the center of the Iraqi journalist of academics, journalists and professionals from male and female and from different DETAILS Press and professions. It was selected sample of this intentional object-center and various job descriptions. The sample size has been reached (250) single. The research found a set of results including - Satellite most incitement to violence and hatred across the channel programs is the first prize of Mesopotamia and Baghdad channel albaghdadia alsharqiah Third Fourth and Fifth altager.